2008
DOI: 10.1247/csf.08005
|View full text |Cite
|
Sign up to set email alerts
|

Dynein-dependent Movement of Autophagosomes Mediates Efficient Encounters with Lysosomes

Abstract: ABSTRACT. Autophagy is a membrane trafficking pathway that carries cytosolic components to the lysosome for degradation. During this process, the autophagosome, a double-membraned organelle, is generated de novo, sequesters cytoplasmic proteins and organelles, and delivers them to lysosomes. However, the mechanism by which autophagosomes are targeted to lysosomes has not been determined. Here, we observed the real-time behavior of microtubule-associated protein light chain 3 (LC3), which localizes to autophago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
293
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 375 publications
(312 citation statements)
references
References 53 publications
17
293
1
1
Order By: Relevance
“…We isolated APG (enriched in LC3‐II and p62; note that the low amounts of LAMP1 and cathepsin observed in this fraction could represent amphisomes [resulting from fusion of APG and late endosomes]) and AUT (also enriched in both markers but with higher abundance of lysosomal markers (LAMP1, CathB, and mucolipin; Figure 4a ). To determine whether our isolation procedure preserved vesicle‐associated motor proteins, we performed immunoblots for the minus‐end‐directed motor dynein (Jahreiss et al., 2008; Katsumata et al., 2010; Kimura, Noda & Yoshimori, 2007; Kimura et al., 2008) and the plus‐end‐directed motor KIF5B (Cardoso et al., 2009; Geeraert et al., 2010) previously described to contribute to trafficking of autophagic compartments. Immunofluorescence and immunoblot for motor proteins (dynein shown in Figure 4a,b and S4a–c) in the isolated fractions confirmed that motors were indeed present on the surface of the isolated APG and were not due to contamination of the preparation with cytosol.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We isolated APG (enriched in LC3‐II and p62; note that the low amounts of LAMP1 and cathepsin observed in this fraction could represent amphisomes [resulting from fusion of APG and late endosomes]) and AUT (also enriched in both markers but with higher abundance of lysosomal markers (LAMP1, CathB, and mucolipin; Figure 4a ). To determine whether our isolation procedure preserved vesicle‐associated motor proteins, we performed immunoblots for the minus‐end‐directed motor dynein (Jahreiss et al., 2008; Katsumata et al., 2010; Kimura, Noda & Yoshimori, 2007; Kimura et al., 2008) and the plus‐end‐directed motor KIF5B (Cardoso et al., 2009; Geeraert et al., 2010) previously described to contribute to trafficking of autophagic compartments. Immunofluorescence and immunoblot for motor proteins (dynein shown in Figure 4a,b and S4a–c) in the isolated fractions confirmed that motors were indeed present on the surface of the isolated APG and were not due to contamination of the preparation with cytosol.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of autophagy, the balance of active motor proteins on the surface of autophagosomes has been proposed to prevent their premature or random fusion with lysosomes (Mackeh et al., 2013). In most cells, autophagosome–lysosome fusion occurs mainly in the perinuclear region where it is facilitated through both physical proximity of the organelle and slowing of vesicular trafficking (Kimura, Noda & Yoshimori, 2008; Zaarur et al., 2014). Consequently, efficient positioning of these degradative compartments in the vicinity of the nucleus in a microtubule‐dependent manner is an essential step for the final completion of the autophagic process (Kimura et al., 2008; Monastyrska et al., 2009; Sakai, Araki & Ogawa, 1989).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to defects in the induction process, genetic or functional alterations may occur in the autophagosome maturation, autolysosome formation, or autophagosome clearance processes [14] . For example, when components of the dynein motor machinery, such as dynein, dynactin or tubulin deacetylases, undergo changes, autophagosome-lysosome fusion is impaired, leading to decreased autophagic clearance of protein aggregates and enhanced neurotoxicity in animal models of HD and ALS [15][16][17] . In addition, a recent report indicates that rapamycin (a classic autophagic activator) treatment causes further accumulation of autophagic vacuoles but fails to reduce the mutant SOD1 aggregates in ALS transgenic mice, indicating the possibility of abnormal autophagic flux in ALS [18,19] .…”
Section: Autophagic Flux Defects In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Dynactin 1 (DCTN1), another ALS-causing gene (Puls et al, 2003), mediates the transfer of autophagosome within the cell to facilitate fusion with lysosomes (Jahreiss et al, 2008;Kimura et al, 2008). In Perry syndrome, a complex neurodegenerative disease manifesting mainly with parkinsonism and caused by specific DCTN1 mutations, autophagic impairment is suggested by neuronal aggregates containing p62 in autoptic specimens (Farrer et al, 2009).…”
Section: Accumulation Of Als Pathogenetic Proteins and Autophagymentioning
confidence: 99%